CONCESSION LEGISLATION OF THE RUSSIAN FEDERATION AND THE WTO: THE DOCTRINE AND PRACTICAL IMPLEMENTATION - Natalia V. Kuris; Vladimir N. Kuris (Вестник Северо-Кавказского федерального университета)
In thе article the concession legislation of the present from positions of scientists, and also it practice in the form of the Federal law from July, 21st, 2005 №115 «About concession agreements» is investigated. The basic characteristics of the Law are defined, and also the author's concept of differentiation between the concession agreement and the Production Sharing Agreement is offered. Also the presented article is devoted to the concession legislation from the standpoint of it’s unification and harmonization on the basis of recommendation of the World Trade Organization acts.